On statistical convergence of order ? in partial metric spaces - Bayram, Erdal; Bektas, Cigdem A.; Altin, Yavuz (Walter de Gruyter Gmbh, 2024)
The present study introduces the notions of statistical convergence of order alpha and strong p-Cesaro summability of order alpha in partial metric spaces. Also, we examine the inclusion relations between these concepts. In addition, we introduce the notion of lambda-statistical convergence of order alpha in partial metric spaces while providing relations linked to these sequence spaces.
Keywords: Statistical convergence; partial metric space; Cesaro summability